The Dead Sea scrolls and Pauline literature - Rey, Jean-Sébastien. (Studies on the Texts of the Desert of Judah, 2014)
The relationships between Pauline literature and the Dead Sea scrolls have fascinated specialists ever since the latter were first discovered. Now that all the Qumran scrolls have been published, it is possible to see more clearly the amplitude and impact of this corpus on first century Judaism. This book offers some syntheses of the results obtained in the last decades, and also opens up new perspectives, by highlighting similarities and indicating possible relationships between these various writings within Mediterranean Judaism. In addition, the authors wish to show how certain traditions spread, evolve and are reconfigured in ancient Judaism as they meet new religious, cultural and social challenges.